Clinical characteristics, microbiology and outcomes of a cohort of patients treated with ceftolozane/tazobactam in acute care inpatient facilities, Houston, Texas, USA. Issue 1 (2nd January 2023) - Tran, Truc T; Cabrera, Nicolo L; Gonzales-Luna, Anne J; Carlson, Travis J; Alnezary, Faris; Miller, William R; Sakurai, Aki; Dinh, An Q; Rydell, Kirsten; Rios, Rafael; Diaz, Lorena; Hanson, Blake M; et al.
Abstract: Background: Ceftolozane/tazobactam is a β-lactam/β-lactamase inhibitor combination with activity against a variety of Gram-negative bacteria, including MDR Pseudomonas aeruginosa . This agent is approved for hospital-acquired and ventilator-associated bacterial pneumonia. However, most real-world outcome data come from small observational cohorts. Thus, we sought to evaluate the utilization of ceftolozane/tazobactam at multiple tertiary hospitals in Houston, TX, USA. Methods: We conducted a multicentre retrospective study of patients receiving at least 48 h of ceftolozane/tazobactam therapy from January 2016 through to September 2019 at two hospital systems in Houston. Demographic, clinical and microbiological data were collected, including the infecting bacterial isolate, when available. The primary outcome was composite clinical success at hospital discharge. Secondary outcomes included in-hospital mortality and clinical disposition at 14 and 30 days post ceftolozane/tazobactam initiation. Multivariable logistic regression analysis was used to identify predictors of the primary outcome and mortality. Recovered isolates were tested for susceptibility to ceftolozane/tazobactam and underwent WGS. Results: A total of 263 patients were enrolled, and composite clinical success was achieved in 185 patients (70.3%). Severity of illness was the most consistent predictor of clinical success. Combination therapy with ceftolozane/tazobactam and another Gram-negative-active agent was associated with reduced odds of clinical success (OR 0.32, 95% CI 0.16–0.63). Resistance to ceftolozane/tazobactam was noted in 15.4% of isolates available for WGS; mutations in ampC and ftsI were common but did not cluster with a particular ST. Conclusions: Clinical success rate among this patient cohort treated with ceftolozane/tazobactam was similar compared with previous experiences. Ceftolozane/tazobactam remains an alternative agent for treatment of susceptible isolates of P. aeruginosa .